Factors Influencing Behavioral Intention to Apply Freemium Services in Islamic Lifestyle Digital Applications Using Unified Theory of Acceptance and Use of Technology (UTAUT) - Yan Putra Timur; Ririn Tri Ratnasari; Anwar Allah Pitchay; Dyah Permata Sari; Muhammad Rifqi (Journal of Information Systems Engineering and Business Intelligence)
Background: Islamic lifestyle digital applications (ILDA) are a sector in the rapidly increasing digital halal media and leisure industry. To ensure sustainable revenue for ILDA developers, freemium strategy needs to be implemented. However, there is a lack of research examining the factors that influence the adoption of freemium strategies in ILDA products.